Long-term outcomes of ruptured cerebral arteriovenous malformations in the paediatric population: A retrospective review in a regional hospital in Hong Kong. (August 2019) - Tam, Ka Yue; Lim, Kevin; Zhu, Cannon Xian Lun; Chan, Kit Ying; Poon, Wai Sang; Poon, Darren; Kam, Michael; Cheung, Michael; Wong, Kwok Chu George
Highlights: Good outcome can be achieved in paediatric ruptured bAVM patients. A protocol of microsurgery and radiosurgery can achieve good long term outcome. Most patients recovered well with minor deficit. Abstract: The objective of the study is to evaluate the management outcomes of ruptured cerebral arteriovenous malformations (bAVMs) in the paediatric population in a regional hospital in Hong Kong. We performed a retrospective review between 1 January 1999 and 31 December 2017 for ruptured bAVM in a regional neurosurgical centre in Hong Kong. All other vascular pathologies and unruptured cases were excluded. Thirty-three eligible patients were included for analysis. The median age at presentation was 12 (3–18), with a slight male preponderance. Presenting complaints included headache (60.6%), motor deficits (24.2%), and seizure (6.1%). Glasgow coma scale (GCS) on presentation (median, IQR) was 15 (13–15). bAVMs were lobar in 57.6%, infratentorial in 27.3%, and basal ganglia in 9.1%. Follow-up was 101 ± 61 months and ranged from 24 to 229 months. 12 (36.4%) patients underwent emergency haematoma evacuation with or without bAVM excision because of neurological deterioration in the acute phase. 7 (21.2%) patients underwent interval excision and 11(33.3%) patients underwent stereotactic radiosurgery (SRS). There was no residual bAVM and no Clavien-Dindo complications greater than grade II in interval surgery group. Those who underwent SRS had a significantly higher Spetzler-Martin grade; bAVM obliteration was achieved at 73.3%, without any major symptomatic post-radiosurgery complications. There was 1 (3%) mortality and 30 (90.9%) patients recovered well with minor non-disabling deficits (GOS 5). For paediatric patients with ruptured bAVM, a satisfactory management outcome can be achieved with careful patient selection for surgery and radiosurgery.